PENGEMBANGAN MEDIA PEMBELAJARAN KREATIF UNTUK MENINGKATKAN HASIL BELAJAR PENDIDIKAN AGAMA ISLAM - Badrul Muslim; Mar’atus Sholihah; Silvina Sri Aryani; Annisatun Nasfa Nurmarifah; Muhammad Saputra; Adriansah Dani; Ahmad Zaki; Sabrun Jamil (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Learning media plays an important role in supporting the effectiveness of Islamic Religious Education learning, as it helps teachers deliver materials in a clearer, more engaging, and more meaningful way. Islamic Religious Education does not only focus on cognitive achievement but also emphasizes the development of attitudes and the application of Islamic values in students’ daily lives. Therefore, creative learning media is needed to avoid monotonous learning processes and to increase students’ involvement. This study aims to examine the role and development of creative learning media in Islamic Religious Education and its contribution to improving students’ learning outcomes. The study employed a qualitative approach using library research by reviewing relevant books and scientific journal articles published within the last five years. Data were analyzed through content analysis by organizing and interpreting findings based on key themes related to creative learning media, Islamic Religious Education, and learning outcomes. The results indicate that creative learning media can enhance students’ learning motivation and interest, encourage active participation, and support a deeper understanding of Islamic education materials. In addition, learning media that are designed in accordance with instructional objectives and students’ characteristics have a positive impact on learning outcomes, including knowledge, attitudes, and religious skills. Thus, the development of creative learning media is considered a strategic effort to improve the quality of Islamic Religious Education learning.